Pengaruh Pengalaman Kerja, Pelatihan Kerja, Dan Persepsi Terhadap Efektivitas Sistem Informasi Keuangan Daerah Pada Badan Keuangan Dan Aset Daerah Kota Madiun - Afifu Rohman Afandi; Djuwitawati Ratnaningtyas; Arini Wildaniyati (Universitas Merdeka Madiun, 2024)
This study aims to examine the effect of work experience, job training, and perceptions on the effectiveness of regional financial information systems. This type of research is quantitative. Data collection techniques in this study used questionnaires directly to respondents. Respondents in this study were employees of Badan Keuangan dan Aset Daerah Madiun City. Data analysis was performed using multiple linear regression analysis with the SPSS (Statistical Product and Service Solution) version 25 for windows program. The results of the research hypothesis show that the independent variable work experience is 0.026, the independent variable job training is 0.000, the perception variable is 0.004, and the simultaneous test shows a significance value of 0.000. The results of this study indicate that work experience has a positive effect on the effectiveness of regional financial information systems, job training has a positive effect on the effectiveness of regional financial information systems, and perceptions have a positive effect on the effectiveness of regional financial information systems, as well as work experience, job training, and perceptions simultaneously have an effect on the effectiveness of regional financial information systems. Based on the results of this study, it is hoped that the Badan Keuangan dan Aset Daerah of Madiun City will continue to improve training programs for employees and instill positive perceptions in order to provide good output in terms of the effectiveness of the regional financial information system.